Rare locations of metastastatic renal cell carcinoma: Presentation of three cases - Milović Novak; Lazić Miodrag; Aleksić Predrag; Radovanović Dragan; Bančević Vladimir; Savić Slaviša; Stamenković Dušica; Spasić Dušan; Košević Branko; Perović Dragoljub; Jovanović Mirko (Vojnosanitetski Pregled)
Introduction. Metastatic renal cell carcinoma (RCC) frequently spreads not only to neighboring lymph nodes, but also to distant organs, including the lungs, liver, bones and brain. Case report. We presented three cases of RCC with colon metastasis. In the first, 63-year-old patient, after left nephrectomy followed with lyphadenectomy in paraaortic lymph node, left hemicolectomy was done due to RCC metastasis in rectosigmoid colon. In the second, 35-year-old patient, left radical nephrectomy was followed two years later with partial right nephrectomy, lung metastasectomy, small bowel and coecum resection and right orchiectomy all as separate procedures in different time intervals. The patient died from brain and bone metastases two years after the first surgery. The third, 35-year-old patient, had right nephrectomy followed by repeted lymphadenectomies after 6, 12 and 24 months. Four years later RCC spreaded to coecum and right hemicolectomy was performed. Conclusion. RCC treated with nephrectomy should be carefully followed up with imaging methods as a proper treatment of RCC metastases to distant organs could be important for a patient survival.